2005
DOI: 10.1369/jhc.4a6534.2005
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Modeling of Oral HIV Transmission in Human Palatine Tonsil

Abstract: The majority of newly acquired HIV infections are believed to occur following transmission of virus infectivity across mucosal surfaces, although many mechanistic details still remain unresolved. We have used human ex vivo organ cultures and primary cell populations to analyze the cellular and molecular basis for mucosal HIV transmission. By using human palatine tonsil from routine tonsillectomies and semen from HIV-positive donors, we have created an experimental equivalent to oral HIV transmission. HIV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 50 publications
(60 reference statements)
0
34
0
Order By: Relevance
“…Normal " morphology equates to a range of variance away from the idealized state and, equally importantly, epithelial surface structure and barrier characteristics may change from normal to abnormal within 50 -100 m. Every piece of human tissue is different, and we have evidence from both histological and biochemical analyses that large differences can occur in adjacent regions on the surface of a single piece of tissue. 105,107,121 These same conclusions regarding tissue variability also apply to macaques. The critical point here is that, although variability in macaque FRT morphology undoubtedly affects macaque susceptibility to SIV infection, 63,122 -124 further insights into the specific events underlying HIV-1 transmission can only be derived by direct analysis of human premenopausal FRT.…”
Section: Practical Considerations For Experiments With Human Tissue Smentioning
confidence: 64%
See 1 more Smart Citation
“…Normal " morphology equates to a range of variance away from the idealized state and, equally importantly, epithelial surface structure and barrier characteristics may change from normal to abnormal within 50 -100 m. Every piece of human tissue is different, and we have evidence from both histological and biochemical analyses that large differences can occur in adjacent regions on the surface of a single piece of tissue. 105,107,121 These same conclusions regarding tissue variability also apply to macaques. The critical point here is that, although variability in macaque FRT morphology undoubtedly affects macaque susceptibility to SIV infection, 63,122 -124 further insights into the specific events underlying HIV-1 transmission can only be derived by direct analysis of human premenopausal FRT.…”
Section: Practical Considerations For Experiments With Human Tissue Smentioning
confidence: 64%
“…We have used a multi-microscope approach to visualize a dynamic sequence of events that occurs when HIV-1 virions or HIV-1-infected cells are deposited onto intact human epithelial surfaces. 105,107 In many experiments, fluorescently labeled latex particles (0.1 and 4.0 m diameter spheres; Invitrogen: Molecular Probes, Eugene, OR; approximate representations of HIV-1 virions and HIV-1-infected lymphocytes, respectively) have been used to demonstrate that inert particles readily interact with mucosal surfaces in the FRT. Surface binding and tissue penetration were examined by time-lapse confocal microscopy, using fresh unfixed human tissues that contained live cells.…”
Section: Progression From Hiv-1 Exposure To Primary Hiv-1 Infectionmentioning
confidence: 99%
“…Expanded primary cell populations were determined to be fibroblasts by strong positive staining with antibodies directed against vimentin. No detectable staining with antibodies directed against cytokeratins was observed (30).…”
Section: Methodsmentioning
confidence: 96%
“…In earlier studies, we reported the potential of GAS to invade human primary tonsil epithelial cells (PHTF) in vitro (8). As we have continued to work with tonsil explants, we have identified considerable variability in the populations of primary cells that can be grown out (30). For these studies, we deliberately focused on PHTF as a potential source of TGF-␤1 because PHTF can be propagated in larger numbers to support biochemical analyses.…”
Section: Tgf-␤1 Enhances Expression Of ␣5 Integrin and Invasion Of Phtfmentioning
confidence: 99%
“…Tissue pieces in agarose were infected and processed as described (22,23). Alternatively, in some infections, cervical tissue was submerged in cell-free virus and then the tissue was cultured on collagen sponges at the gas-medium interface.…”
Section: Methodsmentioning
confidence: 99%